Anogenital Ulcers: An Unusual Manifestation of Invasive Aspergillosis. (18th December 2018) - Vargas, Pablo; Valenzuela, Fernando; Kaplan, Viera; Yumha, Jacob; Arceu, Montserrat; Morales, Claudia
Abstract : Aspergillus spp. is one of the most ubiquitous fungi but generally does not cause disease in immunocompetent patients. It is the second most frequent agent of opportunistic fungal infections, after Candida albicans, with a rise in its incidence on recent years. Invasive fungal diseases represent an important cause of morbidity and mortality. Its origin can be primary, in relation to a cutaneous injury, or secondary, by extension from contiguous tissues, or by hematogenous spread, usually in the context of pulmonary aspergillosis. In this report, we describe the case of an elderly woman with invasive aspergillosis that manifested with anogenital and skin ulcers, with unfavorable outcome, despite intensive therapy and intravenous antifungals.